8-7x-3=-59+4x-13

Simple and best practice solution for 8-7x-3=-59+4x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-7x-3=-59+4x-13 equation:


Simplifying
8 + -7x + -3 = -59 + 4x + -13

Reorder the terms:
8 + -3 + -7x = -59 + 4x + -13

Combine like terms: 8 + -3 = 5
5 + -7x = -59 + 4x + -13

Reorder the terms:
5 + -7x = -59 + -13 + 4x

Combine like terms: -59 + -13 = -72
5 + -7x = -72 + 4x

Solving
5 + -7x = -72 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
5 + -7x + -4x = -72 + 4x + -4x

Combine like terms: -7x + -4x = -11x
5 + -11x = -72 + 4x + -4x

Combine like terms: 4x + -4x = 0
5 + -11x = -72 + 0
5 + -11x = -72

Add '-5' to each side of the equation.
5 + -5 + -11x = -72 + -5

Combine like terms: 5 + -5 = 0
0 + -11x = -72 + -5
-11x = -72 + -5

Combine like terms: -72 + -5 = -77
-11x = -77

Divide each side by '-11'.
x = 7

Simplifying
x = 7

See similar equations:

| 5(x)-20=60 | | http://www.geteasysolution.com/1a-15=4a-3 | | (5x-9)+(10x+10)= | | 8x-6=4x+38 | | 5s-26=59 | | 3y=5x+18 | | y(3y+11)=4 | | 4s+27=91 | | y(3y+11)=11 | | 4y+16=6y+2 | | 10=s/7-1 | | x-3=17.5 | | 6(X-2)+10=6X-1 | | 5(x-7)+31=5X-4 | | -8(9-10)/2= | | -16+80=-160 | | .5(x-60)=25+6x | | x+7=2x+54 | | 2x+3y=4z+250 | | X+(X*.42)=27079 | | -16-80=-160 | | 17+1.50x=11+2.75h | | 11+5p=13 | | (4x^6w^2-2xw^7)/2xw^2 | | 1+b-13=12-4b-2b | | 2f-18=-24 | | 4ad+2da= | | 6-3(0+3)= | | 2(x-4)-4x=o | | 21x-2=10x-4 | | 2(3x-5)=4(3x+1) | | 46=2u+14 |

Equations solver categories